2021
DOI: 10.1088/1361-6463/abf677
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of size-selected Ag-clusters on Au-thin films: a composition study with in-situ XPS analysis at an elevated temperature

Abstract: In this paper, we describe a novel method of synthesis of bimetallic Ag–Au alloy nanoparticles with an estimated Ag to Au concentration ratio of ∼3:1 by using a gas-aggregation cluster source. The real time chemical changes occurred on the surface of the alloy film during different stages of annealing at an elevated temperature are observed by in-situ x-ray photoelectron spectroscopy analysis. It is found that the concentration of both Ag and Au of the alloy film simultaneously decreases with the increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…From these HR-XPS spectra of core level Ag 3d, the positions of the doublet peaks, that is, Ag 3d 5/2 and Ag 3d 3/2 , are observed at BE values 368.1 and 374.1 eV, respectively. These assigned BE values of Ag cluster aggregates agree with the previously reported values for metallic Ag NPs. From the literature reports, it is found that the formation of silver oxides causes BE shifts of Ag 3d peak toward a lower value. However, in the present case, we have not noticed any significant BE shifts of Ag 3d peaks which confirms that oxidation of Ag nanostructures does not occur during their deposition.…”
Section: Resultssupporting
confidence: 91%
“…From these HR-XPS spectra of core level Ag 3d, the positions of the doublet peaks, that is, Ag 3d 5/2 and Ag 3d 3/2 , are observed at BE values 368.1 and 374.1 eV, respectively. These assigned BE values of Ag cluster aggregates agree with the previously reported values for metallic Ag NPs. From the literature reports, it is found that the formation of silver oxides causes BE shifts of Ag 3d peak toward a lower value. However, in the present case, we have not noticed any significant BE shifts of Ag 3d peaks which confirms that oxidation of Ag nanostructures does not occur during their deposition.…”
Section: Resultssupporting
confidence: 91%
“…The three oxygen species represented by peaks with BE lower than 531.5 eV gradually form on the surface as the temperature increases. Based on assignments from previous literature, O 1s having BE values above 532.1 eV are mainly attributed to carbon-containing intermediates. Therefore, we denote them as O C1 , O C2 , and O C3 , respectively. Because the scope of this work is to discuss oxygen reaction intermediates formed on silver during the oxidation of ethylene, we will not discuss in detail these species.…”
Section: Resultsmentioning
confidence: 99%
“…One common way for generating clusters is to bombard of substrates with laser pulses, electrons and so on [14][15][16][17][18][19][20], which have also been employed to produce nitrogen clusters [21][22][23][24][25][26][27][28][29][30][31][32]. For example, the nitrogen discharges have been used to generate the linear centrosymmetric ground state of the N 4…”
Section: Introductionmentioning
confidence: 99%